Analysis Of The Influence Of Digital Financial Literacy On Fintech Financing Decisions And Its Impact On Msme Financial Management In Lalabata Subdistrict, Soppeng Regency - Masyadi Masyadi; Sukma Aini; Mutmainna Andi Sudirman; Andi Sonia (GENTARA: management and accounting research, 2026)
The rapid growth of digital financial services has expanded access to financing for micro, small, and medium enterprises (MSMEs), particularly through fintech-based products such as peer-to-peer lending and buy-now-pay-later schemes. However, the complexity of digital financing features and risks requires adequate digital financial literacy to support sound funding decisions and sustainable financial management. This study analyzes the influence of digital financial literacy on fintech funding decisions and its impact on MSME financial management in Lalabata District, Soppeng Regency. Using a quantitative, causal-associative design, data were collected from 120 MSME owners/managers through a structured Likert-scale questionnaire. The data were analyzed using descriptive statistics, reliability testing, and regression-based mediation analysis with SPSS. The results show that the level of digital financial literacy among MSMEs is high (M = 3.72), fintech funding decision quality is high (M = 3.56), and MSME financial management is high (M = 3.52), although separation between personal and business finances remains moderate (M = 3.38). Regression analysis indicates that digital financial literacy significantly influences fintech funding decisions (B = 0.63; p < 0.001; R² = 0.40). Furthermore, fintech funding decisions significantly affect MSME financial management (B = 0.55; p < 0.001), while digital financial literacy also has a direct positive effect on financial management (B = 0.21; p = 0.003). Mediation testing confirms partial mediation, with an indirect effect of 0.35 (p < 0.001), implying that improved literacy strengthens financial management partly through better fintech funding decisions. These findings highlight the importance of strengthening digital financial literacy programs that emphasize total cost calculation, repayment planning, and financial discipline, alongside initiatives encouraging the separation of personal and business finances to improve MSME financial resilience